Mergers and acquisitions, entrepreneurship and innovation - Weber, Yaakov; Tarba, Shlomo Y. (Bingley, U.K. : Emerald, 2016)
This volume of Technology, Innovation, Entrepreneurship and Competitive Strategy is devoted to research aimed at understanding success and failure factors of mergers and acquisitions in entrepreneurial firms. Research topics offer insights into the relationships of performance factors in all stage of M&As, such as planning, negotiation and post-merger integration. Contributions are multidisciplinary and cross-cultural, and tackle key issues from a variety of theoretical and empirical perspectives.
Entrepreneurial integrations skills: knowing what you acquire to integrate it / Florian Bauer, Svante Schriber, David R. King, Borislav Uzelac -- Acquisitions and open innovation - a literature review and extension / Christina O<U+0308>berg -- Managerial retention in cross-border acquisitions: examining institutional influence / Rich A. Devine, Ka<U+0301>tia de Melo Galdino, Bruce T. Lamont -- Strategic media venturing: private equity investments as a strategic tool for media firms / Tim C. Hasenpusch, Sabine Baumann -- Effectuation spectra in Chinese high-tech entrepreneurship: domain-specific logic orietnations and cross-border M&A / Yipeng Liu, Andrew Isaak -- Why good things may not happen in knowledge-intensive acquisitions: the neglect of acquired firm's customers / William Y. Degbey.
Includes bibliographical references.
Print version record
Keywords: Business & Economics -- Strategic Planning; Business strategy; Consolidation and merger of corporations; Corporate reorganizations